(untitled) (Journal of Medicine, 2016)
Background: Aims and Objectives - 1) to do a comparative evaluation of ultrasonography and computed tomography in pancreatic lesions and assess their role as a useful diagnostic tool. 2) To correlate the USG and CT findings with fine needle aspiration cytology (FNAC)/ histopathological findings/ laboratory tests / therapeutic follow up wherever performed, Material and Methods: The present study was carried out in the Department of Radio-diagnosis, Maharishi Markandeshwar Institute of Medical Sciences and Research, Mullana, Ambala. Thirty patients presenting with signs and symptoms of suspected pancreatic lesions referred from various wards and outpatient departments were included in the study. Results: On USG, inflammatory lesions were diagnosed in 15 cases (50%), and on CT scan, the diagnosis was made in 18 patients (60%). Combining the USG & CT findings of inflammatory lesions, the provisional radiological diagnosis of focal pancreatitis was made in 1 case but it was proven to be adenocarcinoma on FNAC. Provisional diagnosis of adenocarcinoma was made in 8 cases, lymphoma in 2 cases, macrocystic adenoma in 1 case and cystadenocarcinoma in 1 case on both USG and CT scan. However on FNAC, adenocarcinoma was proved in 10 patients, lymphoma was found in one case. Thus the provisional radiological diagnosis was correct in 28 patients (93.7%). Conclusion: Sonography detected pancreatic pathology in 27 cases (90%) but CT scan detected pancreatic lesions in all the 30 patients (100%). Present study had been undertaken to do a comparative evaluation of ultrasonography and computed tomography in pancreatic lesions and correlated the findings with fine needle aspiration cytology (FNAC) / HPE / laboratory tests / therapeutic follow up wherever performed. A need thus exists for multiple studies to produce significant in road towards the appropriate imaging diagnosis of pancreatic pathologies as despite the rapid advances in imaging techniques, the overall impact of these modalities on the management and outcome of patients is still debatable J MEDICINE July 2016; 17 (2) : 66-78